Proline as a formic acid stress protectant during fermentation of glucose to ethanol by Saccharomyces spp. - Oshoma, Cyprian E.; Phister, Trevor G.; Powell, Chris D.; Smart, Katherine A.; Du, Chenyu (Mary Ann Liebert, 2017)
During bioethanol production from lignocellulosic hydrolysates, yeasts are frequently exposed to various forms of fermentation stress. These include nutritional starvation, metabolites production, and fermentation inhibiting compounds produced during pretreatment and hydrolysis of the lignocellulosic material. These inhibitors hamper efficient ethanol production as they can be toxic to the microbes conducting the fermentation. Formic acid is a significant inhibitor released into the hydrolyzates at a concentration of 10–30mM. Previously it was found that proline acts as a compatible solute that enhances yeast tolerance to stress and therefore improves fermentation efficiency. Proline functions in vitro in protein and membrane stabilization, lowering Tm of DNA and scavenging of reactive oxygen species. In this study, the addition of proline to the media in order to improve the tolerance of yeast to formic acid during fermentation was investigated using Saccharomyces cerevisiae NCYC2592 and Saccharomyces arboricolus 2.3319. It was observed that when proline was present at 30mM in the medium, cell growth was enhanced compared to the control medium in fermentations using both S. cerevisiae NCYC2592 and S. arboricolus 2.3319. The cell number obtained in proline-supplemented medium increased by 8–10% for both S. cerevisiae NCYC2592 and S. arboricolus 2.3319. Cells cultivated on proline medium yielded a higher accumulation of ethanol than the control medium in both strains. These results indicate that modification of growth medium with proline can increase formic acid tolerance and the fermentative ability of yeast cells.